Los Supuestos de Flagrancia Delictiva y la Incoación del Proceso Inmediato - Valderrama Quino, Jerilynn Alicia (2017)
In the present work we will analyze the criminal flagrancy suppositions existing in our legislation and how these assumptions are being treated at the moment of initiating the application of the Immediate Process, in order to determine if in all the cases regulated in the procedural norm there is the obligatory to be processed by special way. Within this context, a problematic reality is described in the role of the prosecutors at the moment of the initiation of the immediate process, since often, despite the existence of a criminal flagrante delicto, this does not merit its treatment within an immediate process, but more it is necessary to process it within a common process; nevertheless, the criminal legal system has established the obligation of the prosecutor to initiate said process for being within a supposed flagrancy. That is why an analysis was made of the immediate proceedings brought before the courts of preparatory investigation of the Superior Court of Justice of La Libertad for criminal flagrancy, with the purpose of determining whether all cases of criminal flagrancy necessarily require the initiation of criminal proceedings. an immediate process and, therefore, its processing through the development of it. Arriving to conclude that although it is true there is a legal obligation to initiate an immediate proceeding before a case of criminal flagrancy, this does not mean that it is necessarily processed before an immediate process, because the judge finally through flagrant control can determine that the correct way to process it is that of a common process KEY WORDS: flagrancy, assumptions of flagrancy, immediate process, initiation.